Bioactive Pigments of Monascus purpureus Attributed to Antioxidant, HMG-CoA Reductase Inhibition and Anti-atherogenic Functions - Mohankumari, H. P.; Naidu, K. Akhilender; Narasimhamurthy, K.; Vijayalakshmi, G. (Frontiers in Sustainable Food Systems, 2021)
Monascus purpureus is known to produce pigment molecules. The pigments were extracted from M. purpureus fermented rice. In-vitro antioxidant effects of pigments were observed and presumed to alleviate oxidative stress related atherosclerosis effect in rats fed with high fat diet (HFD) for 14 weeks. The formation of lipid peroxide due to the oxidation of serum lipid was higher in rats fed with HFD. While, the feeding of fermented rice (groups III-V) significantly lowered the formation of lipid peroxide (27.1–51.7%) in serum of rats, indicated antioxidative effect of pigments. In addition, feeding of fermented rice lowered serum cholesterol and triacylglycerol by 44.82 and 45.30%, respectively. Whereas, LDL-cholesterol levels were decreased by 70.12% and HDL-cholesterol increased by 34.58%. The atherogenic indices (LDL/HDL and TC/HDL) were reduced by 77.80 and 61.05%, respectively, in rats fed with fermented rice. These data confirmed the anti-atherosclerotic effect of pigments. Further liver enzyme, 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase activity was significantly inhibited up to 54%. The identification of statins, sterols and fatty acids in fermented rice revealed the HMG-CoA reductase inhibitory activity. This was confirmed by synthesis of lower levels of cholesterol and triacylglycerol in liver of rats fed with fermented rice. Accordingly antioxidant, inhibition of HMG-CoA reductase, anti-atherogenic functions of M. purpureus fermented rice is attributed to the collective effect of bioactive metabolites.